Immunocytochemical heterogeneity of somatostatin‐expressing GABAergic interneurons in layers II and III of the mouse cingulate cortex: A combined immunofluorescence/design‐based stereologic study. Issue 11 (29th December 2015) - Riedemann, Therese; Schmitz, Christoph; Sutor, Bernd
ABSTRACT: Many neurological diseases including major depression and schizophrenia manifest as dysfunction of the GABAergic system within the cingulate cortex. However, relatively little is known about the properties of GABAergic interneurons in the cingulate cortex. Therefore, we investigated the neurochemical properties of GABAergic interneurons in the cingulate cortex of FVB‐Tg(GadGFP)45704Swn/J mice expressing green fluorescent protein (GFP) in a subset of GABAergic interneurons (GFP‐expressing inhibitory interneurons [GINs]) by means of immunocytochemical and design‐based stereologic techniques. We found that GINs represent around 12% of all GABAergic interneurons in the cingulate cortex. In contrast to other neocortical areas, GINs were only found in cortical layers II and III. More than 98% of GINs coexpressed the neuropeptide somatostatin (SOM), but only 50% of all SOM + neurons were GINs. By analyzing the expression of calretinin (CR), calbindin (CB), parvalbumin, and various neuropeptides, we identified several distinct GIN subgroups. In particular, we observed coexpression of SOM with CR and CB. In addition, we found neuropeptide Y expression almost exclusively in those GINs that coexpressed SOM and CR. Thus, with respect to the expression of calcium‐binding proteins and neuropeptides, GINs are surprisingly heterogeneous in the mouse cingulate cortex, and the minority of GINs express only one marker protein or peptide. Furthermore, our observation of overlap between the SOM + and CR + interneuron population was in contrast to earlier findings of non‐overlapping SOM + and CR + interneuron populations in the human cortex. This might indicate that findings in mouse models of neuropsychiatric diseases may not be directly transferred to human patients. J. Comp. Neurol. 524:2281–2299, 2016. © 2015 Wiley Periodicals, Inc. Abstract : GFP‐expressing inhibitory interneurons in layers II–III of the cingulate cortex belong to a subpopulation of somatostatin‐expressing interneurons and represent a highly heterogeneous population of GABAergic interneurons. GIN can be subdivided into at least six distinct neurochemical groups according to their expression of neuropeptides and calcium‐binding‐proteins.